ASSESSMENT OF THE DIAGNOSTIC VALUE OF SERUM CATHEPSIN S AND ITS CORRELATION WITH HDL SUBCLASSES IN PATIENTS WITH NON-HODGKIN’S LYMPHOMA : Cathepsin S and HDL subclasses in lymphoma - Mirjanić-Azarić, Bosa; Stankovic, Sinisa; Radic Savic, Zana; Malcic-Zanic, Dragana; Ninic, Ana; Vukovic, Marija; Nezic, Lana; Skrbic, Ranko; Bogavac-Stanojevic, Natasa (Journal of Medical Biochemistry, 2024)
Background: Recent findings point to the key role of cathepsin S (CTSS) in the survival of malignant cells, as well as the significance of the anti-apoptotic properties of high-density lipoprotein (HDL) that contribute to enhanced cell survival.The purpose of this study is to analyze CTSS as a potential biomarker in lymphoma. Also, in order to better understand the role of CTSS in the origin and development of lymphoma, its association with cystatin C (Cys C), lipids, and inflammatory markers was analyzed. Methods: The study included 90 subjects: 11 Hodgkin (HL) and 44 B-cell non-Hodgkin lymphoma (NHL) patients, and 35 healthy subjects. CTSS was determined using the Invitrogen ELISA kit (Thermo Fisher Scientific, Inc., Waltham, MA, USA).Results: The level of CTSS was significantly higher in NHL patients than in control subjects: 12.20 (9.75-14.57) vs 9.97 (8.44-10.99), P
Keywords: cathepsin S, cystatin C, HDL3a and HDL3b subclasses, apoptosis, Hodgkin and non-Hodgkin lymphoma